Legal Protection for Consumers on the Transfer of Remaining Shopping Coins into Donations (Case Study at Hypermart Surabaya) - Ricardo Tjandra; Juliana Makadala (Journal of Law, Politic and Humanities, 2024)
This final project was written based on the author's experience, who often shopped at minimarkets, supermarkets, and hypermarkets. Cashiers usually take unilateral actions in returning the change, tiny denominations, and often harm consumers. Therefore, the author is interested in compiling a final project titled "Legal Protection for Consumers for Diverting Money from Coin Shopping Remaining into Donations Case Study at Hypermart Surabaya." The purpose of writing this thesis is to identify the form of accountability of business actors for the transfer of the remaining money from shopping into donations by Hypermart business actors in the City of Surabaya and to examine the legal protection for consumers for the transfer of the remaining money from spending into donations by Hypermart business actors in the City of Surabaya. And the academic purpose of writing this thesis is to fulfill the final requirements to get a Bachelor of Law degree at the Faculty of Law, Pelita Harapan University, Surabaya Campus. The results of the analysis in this final project can be concluded that business actors have violated Article 15 of the UUPK, which has carried out coercion by diverting the remaining money from coin shopping into donations without consumer approval.